Nanocomposites in 3D Bioprinting for Engineering Conductive and Stimuli‐Responsive Constructs Mimicking Electrically Sensitive Tissue. Issue 2 (8th February 2022) - Züger, Fabian; Marsano, Anna; Poggio, Martino; Gullo, Maurizio R.
Abstract : Tissue Engineering Combining biofabrication techniques with intrinsic conductive additives, i.e., nanocomposites, is a promising way to achieve relevant physiological conditions in electrophysiological human tissue like cardiac and neural tissue. In article number 2100108, Fabian Züger, Maurizio R. Gullo, and co‐workers review current research on bioprinted conductive and stimuli responsive tissues using nanocomposites. The cover image shows an artistic close view on biofabricated cardiac tissue emended in a nanocomposite doped hydrogel. Image by M. Gullo, Sivu.